Multi-layer Radiation Shielding Design For Compact Proton Therapy System Using Monte Carlo Simulation - Aliyah, Fitrotun (2024)
Proton therapy has emerged as a highly effective treatment for various cancers due to its precision in targeting tumor cells while minimizing radiation exposure to surrounding healthy tissues. However, the design of compact proton therapy facilities poses significant challenges, particularly in terms of shielding requirements, cost, and environmental impact. This study aims to develop a novel shielding design for proton therapy systems that complies with regulatory dose limits while reducing the overall cost and footprint by utilizing alternative materials through a multilayer structure model. The research begins with the characterization of natural aggregate and steel slag as potential alternative materials for concrete admixture, then continues with experimental evaluations of radiation attenuation properties using PuBe, LINAC, and CT-Scan as radiation sources. To further develop and optimize the shielding design, the study employed Monte Carlo simulations using the Particle and Heavy Ion Transport code System (PHITS). These simulations facilitated the creation of innovative shielding configurations, incorporating both single-layer and multilayer structures composed of Portland concrete (PC), steel slag concrete (SSC) , iron (Fe), borated polyethylene (BPE), and recycled high-density polyethylene (HDPE). The experiment results demonstrate that steel slag concrete offers superior radiation shielding performance compared to conventional concrete. The PHITS simulation results demonstrate that the material combination model of PC-SSC on the treatment room wall and PC-SSC-Fe-HDPE on the Maze 1 wall is the optimal configuration with ambient dose equivalent rate value ranging from 13 to 773 mSv/year.